Phase change energy storage material as well as preparation method and application thereof
By uniformly adhering magnetic particles in the composite phase change material and using graphene oxide, a phase change energy storage material with multi-energy conversion performance is formed, which solves the leakage and supercooling problems of the material during the phase change process, and achieves multifunctional energy conversion and storage.
Patent Information
- Application Number
- CN202510190858.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-25
- Filing Date
- 2025-02-20
- Publication Date
- 2025-06-13
AI Technical Summary
Composite phase change materials are prone to leakage and overcooling during phase change, limiting their application range.
By uniformly attaching magnetic particles to non-metallic mineral materials and using graphene oxide, a multifunctional phase change energy storage material that converts multiple energy sources into each other, has photothermal, electric, and magnetothermal conversion properties.
The material exhibits good performance in energy conversion, has excellent thermal conductivity, good cycling stability and high phase transition latent heat, which can be effectively used for energy storage and release, broadening its application range.
Smart Images

Figure BDA0005279959900000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of phase change energy storage materials, and particularly to phase change energy storage materials, their preparation methods and applications. Background Art
[0002] Phase change energy storage is a type of thermal energy storage that utilizes the heat storage characteristics of phase change materials to store or release heat, thereby achieving a certain regulation and control of the temperature of the environment around the phase change materials, changing the spatio-temporal distribution of energy use, and improving the energy use efficiency. Thermal energy storage technology is the key to solar energy utilization. Due to factors such as its ability to achieve thermal energy storage, improve energy utilization efficiency, and solve the relationship between energy supply and demand imbalance, it has been widely applied in fields such as energy-saving buildings, utilization of industrial waste heat, and medical supplies.
[0003] The key problem in solving the heat storage technology is the selection of materials. The types of energy storage materials are mainly divided into sensible heat storage materials, chemical energy storage materials, and latent heat storage materials. Among them, sensible heat storage materials mainly use the temperature change process of the substance itself to store heat, and because of its relatively simple operation method, it is commonly used as an early way to store sensible heat. Chemical energy storage materials mainly store the heat of chemical reactions in chemical media. The forward reaction is endothermic, and the reverse reaction releases heat, but chemical reactions may cause dangerous situations and may cause environmental pollution. Compared with the above methods, latent heat storage materials such as paraffin, polyethylene glycol, and hydrated salts are more concerned because of their advantages such as high latent heat, high energy storage density, and low price. When the phase change material undergoes a phase change, it stores and releases energy by absorbing and releasing heat. However, this phase change material also has obvious defects, such as leakage and supercooling problems during the phase change process. Summary of the Invention
[0004] The main object of the present invention is to propose a phase change energy storage material, its preparation method and application, aiming to solve problems such as leakage and supercooling of composite phase change materials, and on the basis of photothermal conversion, endow the material with excellent magnetothermal conversion and electrothermal conversion properties.
[0005] To achieve the above object, the present invention proposes a phase change energy storage material, which includes the following raw material components: non-metallic mineral materials, phase change materials, graphene oxide, and magnetic particles.
[0006] In one embodiment, by mass, the phase change energy storage material includes the following raw material components: 10-20 parts of non-metallic mineral materials, 70-80 parts of phase change materials, 1-5 parts of graphene oxide, and 1-5 parts of magnetic particles.
[0007] In one embodiment, the non-metallic mineral materials include at least one of kaolin, bentonite, vermiculite, attapulgite clay, and diatomite; and / or,
[0008] The phase change material includes at least one of paraffin, polyethylene glycol, fatty acid, fatty acid ester, and hydrate salt; and / or,
[0009] The magnetic particles are prepared from a magnetic precursor solution, which includes at least one of ferrous sulfate solution, ferric sulfate solution, ferrous chloride solution, ferric chloride solution, cobalt sulfate solution, and cobalt chloride solution.
[0010] The present invention also provides a method for preparing a phase change energy storage material, including the following steps:
[0011] S10. Attach the magnetic particles to a non-metallic mineral material to obtain a magnetic non-metallic mineral material;
[0012] S20. Mix the phase change material with the magnetic non-metallic mineral material to obtain a composite phase change material;
[0013] S30. Immerse graphene oxide into the composite phase change material to obtain a phase change energy storage material.
[0014] In one embodiment, step S10 includes the following steps:
[0015] Mix the non-metallic mineral material and the magnetic precursor with water respectively to obtain a non-metallic mineral material dispersion and a magnetic precursor solution. Drop the magnetic precursor solution into the non-metallic mineral material dispersion at 50 - 80 °C to obtain a mixed solution, filter, take the solid and dry it to obtain a magnetic non-metallic mineral material.
[0016] In one embodiment, when dropping the magnetic precursor solution into the non-metallic mineral material dispersion in step S10, a pH regulator is also added, and the pH value of the mixed solution is 4.5 - 6.5; and / or,
[0017] In the non-metallic mineral material dispersion, the mass ratio of the non-metallic mineral material is 4% - 8%; and / or,
[0018] The molar concentration of the magnetic precursor solution is 0.5 mol / L - 1 mol / L.
[0019] In one embodiment, step S20 includes the following steps:
[0020] S21. Heat the phase change material to a molten state, and then mix it with the magnetic non-metallic mineral material to obtain a mixed phase change material;
[0021] S22. Vacuum impregnate the mixed phase change material at a temperature of 50 - 70 °C, a pressure of 0.08 - 0.1 MPa, and a duration of 24 - 36 h.
[0022] In one embodiment, in step S20, the mass ratio of the phase change material to the magnetic non-metallic mineral material is (2-8):1.
[0023] In one embodiment, step S30 includes the following steps:
[0024] After mixing graphene oxide with absolute ethanol, mix it with water to obtain a graphene oxide dispersion. Immerse the composite phase change material in the graphene oxide dispersion, take it out and dry it to obtain a phase change energy storage material;
[0025] Wherein, the mass ratio of the graphene oxide to the absolute ethanol is 1:(8-12).
[0026] The present invention also proposes an application of the phase change energy storage material in building materials. The phase change energy storage material includes the phase change energy storage material as described above, or the phase change energy storage material prepared according to the preparation method of the phase change energy storage material as described above.
[0027] The technical solution of the present invention uniformly attaches magnetic particles to non-metallic mineral materials and uses graphene oxide to form a multifunctional phase change energy storage material with mutual conversion between multiple energies. It mainly adapts to the working modes in different scenarios through photothermal - electrothermal - magnetothermal conversion, increases the electrothermal and magnetothermal conversion performances without changing the original performance, and makes its application range wider. In addition, it also shows good performance in energy conversion. The obtained material has excellent thermal conductivity, good cycle stability, and high phase change latent heat, and can be well used for energy storage and release. Detailed implementation manners
[0028] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0029] It should be noted that for those not specifying specific conditions in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. For reagents or instruments without indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase. In addition, the meaning of "and / or" appearing throughout the text includes three parallel scenarios. Taking "A and / or B" as an example, it includes Scenario A, or Scenario B, or the scenario where both A and B are satisfied simultaneously. Furthermore, the technical solutions between various embodiments can be combined with each other, but it must be based on the fact that those of ordinary skill in the art can implement them. When the combination of technical solutions leads to contradictions or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts belong to the scope of protection of the present invention.
[0030] Phase change energy storage is a type of thermal energy storage that utilizes the heat storage characteristics of phase change materials to store or release the heat therein, thereby achieving a certain regulation and control of the temperature of the environment around the phase change material, changing the spatio-temporal distribution of energy use, and improving the energy use efficiency. And thermal energy storage technology is the key to solar energy utilization. Due to factors such as its ability to achieve thermal energy storage, improve energy utilization efficiency, and solve the relationship between energy supply and demand imbalance, it has been widely applied in fields such as energy-saving buildings, utilization of industrial waste heat, and medical supplies.
[0031] The key to solving the crucial problems of heat storage technology is the selection of materials. The types of energy storage materials are mainly divided into sensible heat storage materials, chemical energy storage materials, and latent heat storage materials. Among them, sensible heat storage materials mainly utilize the temperature change process of the substance itself to store heat. Because its operation method is relatively simple, it is commonly used as an early way to store sensible heat. Chemical energy storage materials mainly store the heat of chemical reactions in chemical media. The forward reaction is endothermic, and the reverse reaction releases heat. However, chemical reactions may pose dangerous situations and may cause environmental pollution. Compared with the above methods, latent heat storage materials such as paraffin, polyethylene glycol, and hydrated salts are more concerned because of their advantages such as high latent heat, high energy storage density, and low price. When the phase change material undergoes a phase change, it stores and releases energy by absorbing and releasing heat. However, phase change materials also have obvious defects. Their leakage during the phase change process and the supercooling problem will hinder the development of phase change materials. To solve the problems encountered in the phase change process of PCM, the simplest method is to load the phase change material into a porous structure substance, such as kaolin, vermiculite, etc., which can effectively prevent the phase change material from leaking during the phase change process. At the same time, it can also provide reliable support for the phase change material during the phase change process, which can better apply it in fields such as building materials and solar power generation.
[0032] Phase change energy storage technology has unique advantages and characteristics in current thermal energy storage technologies. Due to its high energy storage density, small size, constant temperature control, significant energy-saving effect, wide range of phase change temperature selection, etc., and it is easy to control, it has important application value and broad prospects in the fields of aerospace, solar energy utilization, heating and air conditioning, power supply system optimization, medical engineering, military engineering, heat storage buildings, and extreme environment clothing.
[0033] To solve the problems of leakage, heat conduction, and electrical conduction of composite phase change materials, the design of functional carriers is crucial. In this project, a loose and porous non-metallic mineral material is used as the substrate, and magnetic particles are uniformly attached to the carrier material through chemical modification. By means of vacuum impregnation, molten stearic acid is loaded into the magnetic non-metallic mineral material in a vacuum drying oven, and then graphene oxide is immersed in the composite material physically to enable it to have good electrical conductivity. Thus, the prepared phase change energy storage material with multi-energy conversion performance has high latent heat and excellent photo-thermal, electro-thermal, and magneto-thermal conversion performances. Therefore, this new composite material has good potential in practical applications.
[0034] In view of this, the present invention proposes a phase change energy storage material, which comprises the following raw material components: non-metallic mineral material, phase change material, graphene oxide, and magnetic particles.
[0035] The technical solution of the present invention forms a multifunctional phase change energy storage material with mutual conversion between multiple energies by uniformly attaching magnetic particles to the non-metallic mineral material and using graphene oxide. It mainly adapts to the working modes in different scenarios through photo-thermal - electro-thermal - magneto-thermal conversion, adding electro-thermal and magneto-thermal conversion performances without changing the original performance, and making its application range wider. In addition, it also shows good performance in energy conversion. The obtained material has excellent thermal conductivity, good cycle stability, and high phase change latent heat, and can be well used for energy storage and release.
[0036] In one embodiment, by mass, the phase change energy storage material comprises the following raw material components: 10 - 20 parts of non-metallic mineral material, 70 - 80 parts of phase change material, 1 - 5 parts of graphene oxide, and 1 - 5 parts of magnetic particles.
[0037] The technical solution of the present invention can achieve efficient heat energy storage and release by using non-metallic mineral materials as the matrix and combining 70 to 80 parts of phase change materials. By adding 1 to 5 parts of graphene oxide, according to the excellent thermal conductivity of graphene oxide, the heat conduction efficiency inside the entire composite material system can be significantly improved, and the temperature homogenization speed during the energy storage process can be accelerated. At the same time, graphene oxide has a certain electrical conductivity, which can improve the electrothermal conversion performance of the phase change energy storage material to a certain extent. By adding 1 to 5 parts of magnetic particles, the material can generate or absorb heat in response to changes in an external magnetic field. When an alternating magnetic field is applied, the magnetic particles will undergo the processes of magnetization and demagnetization, and magnetic hysteresis loss and eddy current loss will be generated during this process, which will then be converted into heat energy.
[0038] In one embodiment, the non-metallic mineral material includes at least one of kaolin, bentonite, vermiculite, attapulgite clay, and diatomite; and / or, the phase change material includes at least one of paraffin, polyethylene glycol, fatty acid, fatty acid ester, and hydrate salt; and / or, the magnetic particles are prepared from a magnetic precursor solution, and the magnetic precursor solution includes at least one of ferrous sulfate solution, ferric sulfate solution, ferrous chloride solution, ferric chloride solution, cobalt sulfate solution, and cobalt chloride solution.
[0039] In the technical solution of the present invention, by using at least one of kaolin, bentonite, vermiculite, attapulgite clay, and diatomite as the non-metallic mineral material, not only good physical structure support is provided, but also the overall stability of the material is improved. These mineral materials usually have good heat resistance and chemical inertness, which helps to prevent the leakage or decomposition of the phase change material during long-term use; by using at least one of paraffin, polyethylene glycol, fatty acid, fatty acid ester, and hydrate salt as the phase change material, a large amount of latent heat can be absorbed and released during the phase change process; by using at least one of ferrous sulfate solution, ferric sulfate solution, ferrous chloride solution, ferric chloride solution, cobalt sulfate solution, and cobalt chloride solution to prepare magnetic particles, the magnetothermal effect can be utilized to generate additional heat under the action of an external alternating magnetic field, further improving the magnetothermal conversion efficiency of the energy storage material.
[0040] The present invention also proposes a preparation method of a phase change energy storage material, including the following steps:
[0041] S10. Attach magnetic particles to the non-metallic mineral material to obtain a magnetic non-metallic mineral material;
[0042] S20. Mix the phase change material with the magnetic non-metallic mineral material to obtain a composite phase change material;
[0043] S30. Immerse graphene oxide in the composite phase change material to obtain the phase change energy storage material.
[0044] The energy storage material prepared by the technical solution of the present invention has excellent thermal stability, high-efficient energy storage capacity, intelligent regulation potential and good thermal conductivity, and is applicable to various application scenarios requiring precise temperature control, such as building energy conservation, wearable devices, heat dissipation of electronic devices and other fields.
[0045] In one embodiment, step S10 includes the following steps: after mixing the non-metallic mineral material and the magnetic precursor with water respectively, obtaining a non-metallic mineral material dispersion liquid and a magnetic precursor solution, dropping the magnetic precursor solution into the non-metallic mineral material dispersion liquid at 50-80 °C, filtering, taking the solid and drying it to obtain a magnetic non-metallic mineral material.
[0046] The technical solution of the present invention ensures the full dispersion of the two components in the liquid medium by mixing the non-metallic mineral material and the magnetic precursor with water respectively to form a non-metallic mineral material dispersion liquid and a magnetic precursor solution, so as to achieve a more uniform distribution in the subsequent mixing process; mixing at a temperature of 50-80 °C helps to increase the reaction rate and promote the good adhesion of magnetic particles on the surface of the non-metallic mineral material, and the appropriate temperature range is conducive to the chemical or physical interaction between metal ions or compounds in the magnetic precursor solution and the non-metallic mineral material.
[0047] In one embodiment, in step S10, when dropping the magnetic precursor solution into the non-metallic mineral material dispersion liquid, a pH regulator is further added, and the pH value of the mixed solution is 4.5-6.5; and / or, in the non-metallic mineral material dispersion liquid, the mass ratio of the non-metallic mineral material is 4%-8%; and / or, the molar concentration of the magnetic precursor solution is 0.5 mol / L-1 mol / L.
[0048] The technical solution of the present invention adjusts the pH value to 4.5 - 6.5. Within this pH range, non-metallic mineral materials (such as kaolin, bentonite, etc.) usually exhibit good dispersibility and stability. An appropriate acid-base environment helps prevent particle aggregation and maintain the uniform distribution of the material in water. Moreover, this pH range is also conducive to promoting good bonding between particles when mixing with the magnetic precursor solution subsequently. In some embodiments of the present invention, when the magnetic precursor solution is dropped into the non-metallic mineral material dispersion, the pH regulator is dropped synchronously. Since the magnetic precursor solution is acidic, dropping the pH regulator can maintain the pH value of the mixed solution in a weakly acidic environment, so that magnetic particles can smoothly adhere to the non-metallic mineral material, and reduce the occurrence of the situation where metal ions in the magnetic precursor solution form precipitates in an alkaline environment due to too high pH value and cannot achieve adhesion; by adjusting the mass ratio of the non-metallic mineral material to be 4% - 8%, it ensures that the non-metallic mineral material has sufficient content in the dispersion to form a stable suspension system, and at the same time will not affect its fluidity or cause precipitation due to too high a concentration; by adjusting the molar concentration of the magnetic precursor solution to be 0.5mol / L - 1mol / L, a higher molar concentration means that there are more magnetic precursors per unit volume, which is beneficial to increasing the loading amount of magnetic particles in the final product. At the same time, a precursor solution with an appropriate concentration can form a relatively uniform coating on the surface of the non-metallic mineral material, thus ensuring the consistency and reliability of the magnetic response performance.
[0049] In one embodiment, step S20 includes the following steps:
[0050] S21. Heat the phase change material to a molten state, and then mix it with the magnetic non-metallic mineral material to obtain a mixed phase change material;
[0051] S22. Vacuum impregnate the mixed phase change material, the impregnation temperature is 50 - 70°C, the impregnation pressure is 0.08 - 0.1MPa, and the impregnation duration is 24 - 36h.
[0052] In the technical solution of the present invention, in step S21, after the phase change material is heated to the molten state, it is mixed with the magnetic non-metallic mineral material. This method ensures that the phase change material can fully penetrate into the pores and surface structure of the non-metallic mineral material, thereby forming a uniform and tightly bonded composite material. This good bonding helps to prevent the leakage or separation of the phase change material during multiple thermal cycles; the vacuum impregnation conditions in step S22 are a temperature of 50-70 °C, a pressure of 0.08-0.1 MPa, and a duration of 24-36 hours, which is beneficial to removing air bubbles in the composite material and promoting the phase change material to fill more deeply and uniformly into the pores of the non-metallic mineral material. Moreover, the vacuum environment reduces air resistance, enabling the phase change material to penetrate better into the matrix material under a lower pressure, while avoiding the decomposition or volatilization of the phase change material caused by high temperature, ensuring the quality and stability of the final product.
[0053] In one embodiment, in step S20, the mass ratio of the phase change material to the magnetic non-metallic mineral material is (2-8):1. By setting the mass ratio of the phase change material to the magnetic non-metallic mineral material between 2:1 and 8:1 in the technical solution of the present invention, it can be ensured that the composite material has a sufficient content of the phase change material to achieve efficient energy storage. A higher proportion of the phase change material means a greater latent heat absorption and release capacity, thereby increasing the overall energy storage density.
[0054] In one embodiment, step S30 includes the following steps:
[0055] Mix graphene oxide with absolute ethanol, and then mix with water to obtain a graphene oxide dispersion. Immerse the composite phase change material in the graphene oxide dispersion, take it out and dry it to obtain a phase change energy storage material;
[0056] Wherein, the mass ratio of the graphene oxide to the absolute ethanol is 1:(8-12).
[0057] In the technical solution of the present invention, by first mixing graphene oxide with absolute ethanol and then with water, the dispersibility of graphene oxide in the solvent can be effectively improved. Absolute ethanol helps to break the van der Waals forces between the graphene oxide sheets and prevent agglomeration, thereby achieving a more uniform dispersion to facilitate the formation of an efficient heat conduction network and then accelerating the heat transfer rate; setting the mass ratio of graphene oxide to absolute ethanol to 1:(8-12), such a ratio helps to achieve good dispersion of graphene oxide in absolute ethanol.
[0058] The present invention also proposes an application of the phase change energy storage material in building materials. The phase change energy storage material includes the phase change energy storage material as described above, or the phase change energy storage material prepared according to the preparation method of the phase change energy storage material as described above.
[0059] Since this application adopts all the technical solutions of the above-mentioned all embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be elaborated one by one here.
[0060] The technical solutions of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0061] Embodiment 1
[0062] This embodiment provides a phase change energy storage material, including 75% of the phase change material main body, 20% of the carrier, 3% of the magnetic precursor, and 2% of the conductive material. Among them, the phase change material main body is stearic acid, the carrier is kaolin, the magnetic precursor is ferrous sulfate solution, and the conductive material is graphene oxide.
[0063] This embodiment also provides a preparation method of the phase change energy storage material, including the following steps:
[0064] Step 1: The process of loading magnetic particles of non-metallic mineral materials:
[0065] Under the weak acid condition with a pH value of 5.5, the non-metallic mineral material and water are mixed and stirred evenly at a ratio of 1:16, and then the 1.28 mol / L magnetic precursor solution is added dropwise and stirred evenly at 75 °C. After the reaction is completed, suction filtration and drying are carried out for standby;
[0066] Step 2: The process of loading the phase change material:
[0067] The magnetic non-metallic mineral material and the phase change material in the molten state at 60 °C are stirred until evenly mixed at a ratio of 1:3;
[0068] Step 3: The vacuum impregnation process:
[0069] The uniformly mixed sample is placed in a vacuum drying oven at a temperature of 60 °C and a pressure of 0.09 MPa for impregnation for 24 h until the phase change material is completely immersed in the magnetic non-metallic mineral material;
[0070] Step 4: The process of conductive film coating on the surface of the phase change energy storage material:
[0071] Graphene oxide and absolute ethanol are mixed and ultrasonicated at a ratio of 1:10. The uniformly mixed solution is slowly dropped into pure water. Finally, the sheet-like phase change energy storage material is immersed in the above solution and then taken out and dried to obtain the phase change energy storage material.
[0072] Embodiment 2
[0073] This embodiment provides a phase change energy storage material, comprising 75% of a phase change material main body, 20% of a carrier, 2% of a magnetic precursor, and 3% of a conductive material. Among them, the phase change material main body is stearic acid, the carrier is kaolin, the magnetic precursor is a ferrous sulfate solution, and the conductive material is graphene oxide.
[0074] Example 3
[0075] This embodiment provides a phase change energy storage material, comprising 70% of a phase change material main body, 20% of a carrier, 5% of a magnetic precursor, and 5% of a conductive material. Among them, the phase change material main body is stearic acid, the carrier is kaolin, the magnetic precursor is a ferrous sulfate solution, and the conductive material is graphene oxide.
[0076] Example 4
[0077] This embodiment provides a phase change energy storage material, comprising 80% of a phase change material main body, 10% of a carrier, 5% of a magnetic precursor, and 5% of a conductive material. Among them, the phase change material main body is stearic acid, the carrier is kaolin, the magnetic precursor is a ferrous sulfate solution, and the conductive material is graphene oxide.
[0078] Example 5
[0079] This embodiment provides a phase change energy storage material, comprising 75% of a phase change material main body, 15% of a carrier, 5% of a magnetic precursor, and 5% of a conductive material. Among them, the phase change material main body is stearic acid, the carrier is kaolin, the magnetic precursor is a ferrous sulfate solution, and the conductive material is graphene oxide.
[0080] Comparative Example 1
[0081] This comparative example provides a phase change energy storage material, comprising 75% of a phase change material main body and 25% of a carrier. Among them, the phase change material main body is stearic acid, and the carrier is kaolin.
[0082] Mix the phase change material main body and the carrier in proportion and make into tablets to obtain the phase change energy storage material.
[0083] Comparative Example 2
[0084] This comparative example provides a phase change energy storage material, comprising 75% of a phase change material main body, 20% of a carrier, and 5% of a magnetic substance. Among them, the phase change material main body is stearic acid, the carrier is kaolin, and the magnetic substance is nano-ferroferric oxide.
[0085] Mix the phase change material main body, the carrier, and the magnetic substance in proportion and make into tablets to obtain the phase change energy storage material.
[0086] Comparative Example 3
[0087] This comparative example provides a phase change energy storage material, which includes 75% of the phase change material main body, 20% of the carrier, 2.5% of the magnetic substance and 2.5% of the conductive material. Among them, the phase change material main body is stearic acid, the carrier is kaolin, the magnetic substance is nano-ferroferric oxide, and the conductive material is graphene oxide.
[0088] Mix the phase change material main body, the carrier, the magnetic substance and the conductive material in proportion, and make a film to obtain the phase change energy storage material.
[0089] Comparative Example 4
[0090] This comparative example provides a phase change energy storage material, the raw materials of which include 75% of the phase change material main body, 20% of the carrier, and 5% of the magnetic precursor. Among them, the phase change material main body is stearic acid, the carrier is kaolin, and the magnetic precursor is 1.28 mol / L ferrous sulfate solution.
[0091] Mix the phase change material main body, the carrier and the magnetic precursor in proportion, and make a film to obtain the phase change energy storage material.
[0092] Performance test
[0093] Perform energy conversion performance tests on the phase change energy storage materials provided in Examples 1 to 5 and Comparative Examples 1 to 4. The experimental method is as follows:
[0094] Photothermal conversion performance experiment: A photothermal conversion simulation device (computer, xenon light source, k-type thermocouple and data acquisition device) is used to measure the photothermal conversion performance of the sample. The data acquisition device records the change of the temperature of the phase change energy storage material with light irradiation. The evaluation is carried out according to whether the phase change energy storage material can complete the photothermal conversion process.
[0095] Magnetothermal conversion performance experiment: A magnetothermal conversion simulation device (computer, magnetic field generator, k-type thermocouple and data acquisition device) is used to measure the magnetothermal conversion performance of the sample. The data acquisition device records the change of the temperature of the phase change energy storage material with the magnetic field. The evaluation is carried out according to whether the phase change energy storage material can complete the magnetothermal conversion process.
[0096] Electrothermal conversion performance experiment: An electrothermal conversion simulation device (computer, xenon light source, electric field generator, k-type thermocouple and data acquisition device) is used to measure the electrothermal conversion performance of the sample. The data acquisition device records the change of the temperature of the phase change energy storage material with the voltage. The evaluation is carried out according to whether the phase change energy storage material can complete the electrothermal conversion process.
[0097] The performance test results are shown in Table 1.
[0098] Table 1 Raw material components and energy conversion performance of the phase change energy storage materials in Examples 1 to 5 and Comparative Examples 1 to 4
[0099]
[0100] Through the comparison of the above five groups of examples, it can be clearly seen that different methods of preparing phase change energy storage materials will obviously result in different effects. Simply adding the magnetic substance magnetite to the carrier for compounding, the photo-thermal and magneto-thermal effects are mediocre. However, by chemically modifying the carrier to functionalize it, excellent performance is shown in various properties. Even when the amount of magnetic material and conductive material is reduced, the composite material can still exhibit excellent performance. Thus, the effect of Example 5 is more excellent.
[0101] Under the conditions of solving the problems of phase change material leakage, supercooling, etc., by combining chemical modification with physical means, the magnetic material and the conductive material are firmly grafted and loaded onto the carrier, enabling the material to have excellent magneto-thermal and electro-thermal conversion properties, and more widely broadening the usage scenarios and application scope of the material, and also making it more convenient to utilize in building materials and industrial waste heat.
[0102] The above are only the preferred embodiments of the present invention, and do not limit the patent scope of the present invention accordingly. Any equivalent structural transformation made using the content of the specification of the present invention under the inventive concept of the present invention, or direct / indirect application in other related technical fields, is included in the patent protection scope of the present invention.
Claims
1. A phase change energy storage material, characterized in that: The raw material components include: non-metallic mineral materials, phase change materials, graphene oxide and magnetic particles.
2. The phase change energy storage material according to claim 1, characterized in that: Calculated by weight, the phase change energy storage material includes the following raw material components: 10 to 20 parts of non-metallic mineral materials, 70 to 80 parts of phase change materials, 1 to 5 parts of graphene oxide and 1 to 5 parts of magnetic particles.
3. The phase change energy storage material according to claim 1, characterized in that: The non-metallic mineral material includes at least one of kaolin, bentonite, vermiculite, attapulgite clay and diatomaceous earth; and / or, The phase change material comprises at least one of paraffin, polyethylene glycol, fatty acid, fatty acid ester and salt hydrate; and / or, The magnetic particles are prepared by a magnetic precursor solution, and the magnetic precursor solution includes at least one of a ferrous sulfate solution, a ferrous sulfate solution, a ferrous chloride solution, a ferric chloride solution, a cobalt sulfate solution and a cobalt chloride solution.
4. A method for preparing a phase change energy storage material, characterized in that: The following steps are involved: S10. attaching magnetic particles to the non-metallic mineral material to obtain a magnetic non-metallic mineral material; S20. Mixing the phase change material with the magnetic non-metallic mineral material to obtain a composite phase change material; S30. Immersing graphene oxide into the composite phase change material to obtain a phase change energy storage material.
5. The method for preparing the phase change energy storage material according to claim 4, characterized in that: Step S10 includes the following steps: The non-metallic mineral material and the magnetic precursor are mixed with water respectively to obtain a non-metallic mineral material dispersion and a magnetic precursor solution. The magnetic precursor solution is added dropwise to the non-metallic mineral material dispersion at 50-80° C. to obtain a mixed solution, which is filtered and the solid is dried to obtain a magnetic non-metallic mineral material.
6. The method for preparing the phase change energy storage material according to claim 5, characterized in that: In step S10, when the magnetic precursor solution is added dropwise to the non-metallic mineral material dispersion, a pH adjuster is also added, and the pH value of the mixed solution is 4.5 to 6.5; and / or, In the non-metallic mineral material dispersion, the mass proportion of the non-metallic mineral material is 4% to 8%; and / or, The molar concentration of the magnetic precursor solution is 0.5 mol / L to 1 mol / L.
7. The method for preparing a phase change energy storage material according to claim 4, characterized in that: Step S20 includes the following steps: S21. The phase change material is heated to a molten state, and then mixed with the magnetic non-metallic mineral material to obtain a mixed phase change material; S22. The mixed phase change material is vacuum impregnated at a temperature of 50 to 70° C., an impregnation pressure of 0.08 to 0.1 MPa, and an impregnation time of 24 to 36 hours.
8. The method for preparing a phase change energy storage material according to claim 4, characterized in that: In step S20, the mass ratio of the phase change material to the magnetic non-metallic mineral material is (2-8):
1.
9. The method for preparing a phase change energy storage material according to claim 4, characterized in that: Step S30 includes the following steps: Mixing graphene oxide with anhydrous ethanol and then with water to obtain a graphene oxide dispersion, immersing the composite phase change material in the graphene oxide dispersion, taking out and drying to obtain a phase change energy storage material; Wherein, the mass ratio of the graphene oxide to the anhydrous ethanol is 1:(8-12).
10. Application of a phase change energy storage material in building materials, characterized in that: The phase change energy storage material includes the phase change energy storage material as claimed in any one of claims 1 to 3, or the phase change energy storage material prepared by the preparation method of the phase change energy storage material as claimed in any one of claims 4 to 9.